Pelatihan TOEFL Berbasis Buku “Belajar TOEFL untuk Persiapan Kerja” bagi Siswa SMK Pradana Giri - Doni Hadi Irawan; Muhamad Alfi Khoiruman (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
AbstractEnglish proficiency has become one of the essential competencies for vocational high school (SMK) graduates to face global job competition, particularly in the maritime sector, which demands workers with strong international communication skills. This community service activity aims to improve the English competence of SMK Pradana Giri Banyuwangi students through a TOEFL training program based on the book “Belajar TOEFL untuk Persiapan Kerja” (Learning TOEFL for Job Preparation). The implementation method consisted of several stages, including socialization, an English proficiency pretest, intensive training using the TOEFL guidebook, and a posttest to measure learning improvement. The program also included mentoring sessions on answering strategies and TOEFL simulations contextualized to workplace situations. The results showed a significant improvement in students’ understanding of language structure, vocabulary, and listening and reading skills. This activity demonstrates that a practical, book-based, and contextual training approach effectively motivates students to learn English more applicatively. Therefore, the program makes a tangible contribution to preparing vocational students to be more competitive in both the maritime and global job markets.